تمرينات تعليمية – تدريبية على حواجز بتصميم مقترح وتأثيرها في زمن خطوة الاجتياز للحاجز (1 – 5 – 10) وانجاز ركض 100م حواجز للأعمار (13 – 14) سنة بنين - Rasheed, Intisar (Journal of Physical Education, 2019)
The research aims to identify the impact of exercise training and its impact education- step in passing the hurdles (1-5-10) in the effectiveness of the 100-meter hurdles aged (13-14 years) at the National Center for marathoners to take care of sports talent's (5) players and researcher used the experimental method with the same group as the application platform on the players in the training units during the period (8) weeks have been a check after the completion of the curriculum and then of acquired data were treated statistically as the researcher concluded that exercise educational - training have an impact in a move to pass the barrier Hence the researcher recommended the need to use exercises to develop step in passing efficiency 100-meter hurdles